A systematic literature review on job performance in diverse organizations from 2010 to 2023 - Alqarni, Saqer; Hamsan, Hanina; Mohd Rasdi, Roziah; Abdul Rahman, Haliza (Human Resource Management Academic Research Society, 2023)
Employee performance profoundly influences organizational success, posing a global challenge. This systematic literature review (SLR) investigates job performance dimensions from 2010 to 2023, adhering to PRISMA guidelines. Data were searched via Scopus, Web of Science, PubMed, and Google Books, yielding 3450 records, reduced to 942 post-deduplications. After title and abstract screening, 829 records were excluded, leaving 41 studies for the final review. The findings categorize job performance into three levels: individual, team, and organizational, further divided into process/job performance and outcome performance. Most studies focus on individual-level process/job performance, with limited attention to organizational-level outcome performance. Employee performance's critical role in organizational effectiveness underscores its relevance to researchers and practitioners. The review emphasizes the importance of fostering supportive work environments and providing resources to enhance employee performance, ultimately driving organizational success. These insights are invaluable to optimizing employee performance and bolstering organizational effectiveness.